How open access boosts the societal impact of humanities and social sciences research - Souster, Ellie (Septentrio Conference Series, 2023)
In this poster, we’ll share findings from our open access partnerships in different countries (including the Nordics), showing measurable benefits such as facilitating interdisciplinary collaboration to help solve the world’s most pressing issues. We’re also keen to work with the research community on other innovative ways to accelerate the transition to OA and boost research impact for institutions in Europe. We’ll also present a few case studies of how research influences policy and improves lives, such as: Addressing socio-economic challenges during the COVID-19 pandemic Investigating the socio-cultural impact of UK gendered school sport uniform The article ‘The Impact of long COVID on the UK workforce’ (Reuschke & Houston 2022) was published OA by the University of Southampton through the Jisc Agreement UK in July 2022. It provides evidence of the profound impact of Long COVID on national labour supply. The article has been cited by at least one policy document, published jointly by the think tank Demos and The Physiological Society (Dawson & Phillips 2022). The article ‘Practical, professional or patriarchal? An investigation into the socio-cultural impacts of gendered school sports uniform and the role uniform plays in shaping female experiences of school sport’ (Howard 2023) was published OA by Durham University through the Jisc Agreement on 6 April 2023. It explores how school sport uniform directly impacts female sporting experiences and participation in physical activity, and how uniform policy could be changed to promote greater female sport participation. By 26 April, less than three weeks after publication, the article had already been mentioned in 17 news stories. Although it's too early to measure citations in research and policy documents, the research has already led to new inclusive kit regulations in domestic hockey. We’ll use a collection of datasets as evidence to support our argument that publishing open access increases the visibility and impact of research. It encourages innovation and collaboration and boosts public engagement. As the largest humanities and social sciences publisher in the world, Taylor & Francis is committed to supporting sustainable routes to OA for HSS research communities, who typically have less funding for OA publishing than their peers in STEM.